2019
DOI: 10.1186/s12939-019-1012-4
|View full text |Cite
|
Sign up to set email alerts
|

Languishing in the crossroad? A scoping review of intersectional inequalities in mental health

Abstract: The concept of intersectionality has gradually been introduced to health inequality research, adding depth and breadth to the way inequalities in health are approached. We conducted a scoping review with the purpose to systematically map, describe and analyze the literature about intersectional inequalities in mental health. For eligibility, the study had to analyze and report inequality defined by combinations of socioeconomic position, gender, race/ethnicity, sexual orientation or religion. The mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(36 citation statements)
references
References 53 publications
(110 reference statements)
2
32
0
2
Order By: Relevance
“…Other health disciplines have advanced intersectionality research, including medicine, 66 nursing, 67 psychology, 68 and psychiatry and mental health 69,70 . This work provides important learning opportunities for oral health research.…”
Section: How Could Oral Health Research Benefit From Adopting An Intementioning
confidence: 99%
“…Other health disciplines have advanced intersectionality research, including medicine, 66 nursing, 67 psychology, 68 and psychiatry and mental health 69,70 . This work provides important learning opportunities for oral health research.…”
Section: How Could Oral Health Research Benefit From Adopting An Intementioning
confidence: 99%
“…Health inequalities have been examined along dimensions such as geographical location, income, education, occupation, gender, ethnicity, race, caste, and more (Arcaya, Arcaya, & Subramanian, 2015). Intersectionality has gradually been introduced into research on health inequalities as a way of understanding the complexity and interactions between different social dimensions (Fagrell Trygg, Gustafsson, & Månsdotter, 2019). The central idea of intersectionality is that many intersecting and interacting axes of social division shape how power is distributed in a society.…”
Section: Social Inequalities In Healthmentioning
confidence: 99%
“…Evidence regarding the impact of SES on mental health status has been mixed, possibly due to the fact that it may interact with factors, such as race, to create individualized experiences and perspectives. Indeed, intersectionality theory proposes that demographic factors, including sex, race/ethnicity, SES, and culture interact to form individualized experiences and perspectives which contribute to differences in mental health attitudes, access, and service use [ 20 , 21 , 22 ]. One literature review suggested that low SES was associated with greater self-reported internalizing mental health problems among adolescents [ 23 ], however, data from a national survey found no relationship between SES and internalizing diagnoses [ 7 ].…”
Section: Introductionmentioning
confidence: 99%